CLINICAL MANIFESTATIONS IN POSITIVE COVID 19 PATIENTS WITH AND WITHOUT VACCINATED - Aurora, Wahyu Indah Dewi; Nuriyah, Nuriyah; Sulistiawan, Andika; Darmawan, Armaidi; Maria, Ima; Kusdiyah, Erny (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
ABSTRACTIntroduction: Since the emergence of Emerging Diseases, namely the discovery of a new virus in 2019which was named Covid-19, the World Health Organization (WHO) has established a Pandemic statusthroughout the world. To anticipate the large number of fatalities, it is necessary to have a vaccine toreduce morbidity and mortality. The purpose of this study was to find out the differences in clinicalmanifestations that appeared in patients with positive Covid-19 before and after receiving vaccination.Method: The design of this study was Cross Sectional conducted at the Puskesmas/Clinic in JambiCity from April to October 2022. The number of samples used was 721 samples using the simplerandom sampling technique, the medical records of patients positive for Covid 19 were taken randomlyat the Puskesmas/Clinic/ Hospitals that meet the inclusion criteria will be included as samples.Results: From the results of the study, the most samples were aged 21-30 years (35.2%). Based ongender, there were 330 respondents (45%). From the results of the study, it was found that thepercentage of respondents who had fever (62.41%), coughing (50.5%), body weakness (32.4%), itchingin the throat (21.63%), runny nose/runny nose (44.8%), dizziness/headache (25.65%). Pain in musclesand joints (25.4%), nausea (13.6%), vomiting (5%), diarrhea (5.3%), fever (26.5%), chest pain (5.8%)), loss of sense of smell (20.24%), loss of sense of taste (13.86%), itching of the skin (2.35%), and othersymptoms such as disorders of the eyes, ears, etc. as much as 8.8% .Conclusion: The clinical manifestations of patients who are positive for Covid 19 are milder inrespondents who have been vaccinated compared to those who have not been vaccinated.Keywords: Clinal Manifestation Covid-19, Vaccine